Ethics of sport and athletics theory, issues, and application - Schneider, Robert C.
"Morality in Sport Sport continues to make its presence known throughout the world as it prospers at all levels. Amazingly, there is no end in sight to the popularity and growth of sport. Essential to sport's continued prosperity, growth, and overall livelihood is the sustenance of a firm moral base. It is the goal and hope of the author that you find this textbook to be a useful guide in helping you maintain and build upon the foundation of moral good that is required for sport to exist now and in the future. The need to make good moral decisions in sport is constant. And, although opportunities to make such decisions in sport are seemingly endless, what is "moral" can be somewhat unclear. Given the various perspectives on morality and the lack of clear-cut distinctions between moral and immoral actions, disagreements regarding moral behavior and sport are likely to always exist. However, having a blatant disregard for good moral behavior in sport is difficult to defend from most any position"--Provided by publisher.
CAC Camia (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Sports -- Moral and ethical aspects